Mechanosensory feedback loops during chronic inflammation - Saha, Sarbari; Müller, Dafne; Clark, Andrew G. (Frontiers in Cell and Developmental Biology, 2023)
Epithelial tissues are crucial to maintaining healthy organization and compartmentalization in various organs and act as a first line of defense against infection in barrier organs such as the skin, lungs and intestine. Disruption or injury to these barriers can lead to infiltration of resident or foreign microbes, initiating local inflammation. One often overlooked aspect of this response is local changes in tissue mechanics during inflammation. In this mini-review, we summarize known molecular mechanisms linking disruption of epithelial barrier function to mechanical changes in epithelial tissues. We consider direct mechanisms, such as changes in the secretion of extracellular matrix (ECM)-modulating enzymes by immune cells as well as indirect mechanisms including local activation of fibroblasts. We discuss how these mechanical changes can modulate local immune cell activity and inflammation and perturb epithelial homeostasis, further dysregulating epithelial barrier function. We propose that this two-way relationship between loss of barrier function and altered tissue mechanics can lead to a positive feedback loop that further perpetuates inflammation. We discuss this cycle in the context of several chronic inflammatory diseases, including inflammatory bowel disease (IBD), liver disease and cancer, and we present the modulation of tissue mechanics as a new framework for combating chronic inflammation.